Asosiasi Paparan Iklan Rokok dengan Pengetahuan, Sikap, dan Perilaku Merokok pada Remaja - Nimfa Christina Rachmawati Wibowo; Ari Probandari; Arsita Eka Prasetyawati (Nexus Kedokteran Komunitas, 2012)
Background:Knowledge and attitude are factors influence smoking behavior among teenagers. Previous studies show that cigarette advertisements do not consistently affect on teenagers smoking behavior. This studyaimed to determine the association between cigarette advertisement exposure, knowledge, attitude, and smoking behavior among teenagers. Methods:A cross-sectional study was conducted during March 2012 among 98 students in SMP Negeri 01 Colomadu, Karanganyar. The sampling technique was a multistage cluster sampling. Cigarette advertisement exposure, knowledge, attitude, and smoking behavior data were collected using questionnaires, which were tested for its validity and reliability before. The data analyses used Spearman correlation and Chi-Square tests. Results:The study found a significant relationship between cigarette advertisement exposure and knowledge (r=-0.267; p=0.009). There was no significant relationship between cigarette advertisement exposure and teenagers attitude (r=-0.129; p=0.206). There were no significant relationships between cigarette advertisement exposure 1-10 times per week and past smoking(p=1,000; OR=0,917; CI95% 0,258-3,262),and with current smoking among teenagers (p=1,000; OR=0,971; CI95% 0,931-1,012). Cigarette advertisement exposure more than 11 per week increased a risk for past smoking 2.406 times (p=0,500; Cl95% 0,521-11,104), but not significantly. Conclusions:Cigarette advertisement exposure more than 11 per week associated with teenagers knowledge about cigarette and teenagers' attitude to cigarette and smoking. There is no significant relationship between cigarette advertisement exposure and smoking behavior among teenagers. Keywords:cigarette advertisement, knowledge, attitude, behavior, and smoking.